Design and Development of a Web-Based Project Management Application Using the Kanban System for Team Collaboration - Fakhri Alauddin Tarihoran; Muhammad Irwan Padli Nasution (Ali Institute of Reseach and Publication, 2026)
Lack of coordination and transparency often pose significant challenges in managing project teams. This study aims to develop a web-based project management application that utilizes the Kanban method to improve team efficiency and collaboration. The application was developed using Node.js for the backend, React.js for the frontend, Tailwind CSS for the interface design, and MySQL as the database system. The development process followed the Software Development Life Cycle (SDLC) based on the Waterfall model. The results of black-box testing indicate that all core features — including board, list, and card creation, team management, and task assignment — operate successfully. The application significantly improves team coordination, transparency, and overall work performance.